Community Empowerment through Youth Peer Education in Efforts to Prevent Child Marriage - Siregar, Neny San Agustina; Arisjulyanto, Dedy; Mansur, Tri Noviyanti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Child marriage among adolescents is a social issue that negatively impacts health, education, and social well-being. Mimika Regency has a high rate of child marriage. This study aims to identify the effectiveness of the Community Empowerment program through the peer education method in preventing child marriage among adolescents in Mimika. The research design used is quasi-experimental, with a population of adolescents aged 15-18 years. A sample of 65 respondents was selected using purposive sampling. Data were collected using knowledge and attitude questionnaires that have been tested for validity and reliability, with Cronbach’s alpha values of 0.917 for the knowledge questionnaire and 0.904 for the attitude questionnaire. Data collection began with a pre-test, followed by a post-test after the intervention. The results showed an increase in the mean score of adolescents' knowledge about child marriage from 31.20 before the intervention to 39.28 after the intervention, with a p-value of 0.000 (<α=0.05). Similarly, the mean attitude score toward child marriage increased from 21.32 to 30.98, with a p-value of 0.000. The conclusion of this study indicates a positive effect of Community Empowerment through Peer Education in preventing child marriage in Mimika Regency.